2006
DOI: 10.1068/p5460
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoint and Orientation Influence Picture Recognition in the Blind

Abstract: In the first three experiments, subjects felt solid geometrical forms and matched raised-line pictures to the objects. Performance was best in experiment 1 for top views, with shorter response latencies than for side views, front views, or 3-D views with foreshortening. In a second experiment with blind participants, matching accuracy was not significantly affected by prior visual experience, but speed advantages were found for top views, with 3-D views also yielding better matching accuracy than side views. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…Most sighted adults have difficulty determining how to draw tilted squares in perspective by adjusting angles at vertices (Kennedy, 1993), and the early-blind likely have similar issues, even if they are very familiar with cubes at many orientations (Eriksson, 1998;Heller et al, 2006;Heller et al, 2009;Kennedy, 1993;Picard & Lebaz, 2012). This is a topic that deserves considerable investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most sighted adults have difficulty determining how to draw tilted squares in perspective by adjusting angles at vertices (Kennedy, 1993), and the early-blind likely have similar issues, even if they are very familiar with cubes at many orientations (Eriksson, 1998;Heller et al, 2006;Heller et al, 2009;Kennedy, 1993;Picard & Lebaz, 2012). This is a topic that deserves considerable investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The blind participants in these studies used raised-line pictures (Eriksson, 1998;Hatwell & Martinez-Sarrochi, 2003;Picard & Lebaz, 2012). Also, blind and sighted adults recognize foreshortened pictures of objects fitting a single vantage point to the side of an array of objects (Heller et al, 2006;Heller et al, 2009). In making drawings of houses, the order of success was "from above," then "from the side," and then "three-quarter views" (Heller, Kennedy, & Joyner, 1995)-that is, plan, then elevation, and then three-quarter views.…”
mentioning
confidence: 99%
“…For example, Kennedy (2008), Kennedy and Juricevic (2006), and Heller et al (2006), have all found that people born without sight have the capacity to reproduce concepts such as visual metaphor and perspective without formal education in these concepts. In addition, experimental studies involving the dulling of different senses under laboratory conditions by Driver and Spence (2004) have questioned the notion of the exclusivity of touch as the only perception that can provide effective information, and argue instead that perception is multi-modal, (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Viewpoint effects in visually impaired people with complex objects The first experiment was designed to determine if visual experience would influence viewpoint effects with relatively complex objects. In earlier research with blindfoldedsighted subjects by Heller et al (2006), there were no advantages for top views of these complex objects in the accuracy of matching tangible pictures to solid objects. It was not known if viewpoint effects would be found in visually impaired participants with these relatively complex objects.…”
mentioning
confidence: 99%
“…Experiment 1 was based on experiment 6 in Heller et al (2006), but included samples of visually impaired participants. In experiment 2 the effect of visual experience and the presence of object details on viewpoint effects in haptic pictures was tested.…”
mentioning
confidence: 99%